Ethmoidal encephalocoele presenting as spontaneous cerebrospinal fluid rhinorrhea in an adult - Kumar, Lokesh; Kiran, Narayanam Anantha Sai; VA, Kiran Kumar; M, Venkatesh; Moscote-Salazar, Luis Rafael; Agrawal, Amit (Indian Journal of Case Reports, 2018)
-